Electrical neurostimulation with imbalanced waveform mitigates dissolution of platinum electrodes. (21st September 2016) - Kumsa, Doe; Hudak, Eric M; Montague, Fred W; Kelley, Shawn C; Untereker, Darrel F; Hahn, Benjamin P; Condit, Chris; Cholette, Martin; Lee, Hyowon; Bardot, Dawn; Takmakov, Pavel
Abstract: Objective. Electrical neurostimulation has traditionally been limited to the use of charge-balanced waveforms. Charge-imbalanced and monophasic waveforms are not used to deliver clinical therapy, because it is believed that these stimulation paradigms may generate noxious electrochemical species that cause tissue damage. Approach. In this study, we investigated the dissolution of platinum as one of such irreversible reactions over a range of charge densities up to 160 μ C cm −2 with current-controlled first phase, capacitive discharge second phase waveforms of both cathodic-first and anodic-first polarity. We monitored the concentration of platinum in solution under different stimulation delivery conditions including charge-balanced, charge-imbalanced, and monophasic pulses. Main results. We observed that platinum dissolution decreased during charge-imbalanced and monophasic stimulation when compared to charge-balanced waveforms. Significance. This observation provides an opportunity to re-evaluate the charge-balanced waveform as the primary option for sustainable neural stimulation.